Leader Communication and Follower Identity: How Leader Motivating Language Shapes Organizational Identification through Cultural Knowledge and Fit. (April 2021) - Mayfield, Milton; Mayfield, Jacqueline; Walker, Robyn
This study examines the links between leader communication (as conceptualized through motivating language) and follower organizational identification as mediated by follower cultural knowledge and fit. Results show that motivating language has a positive and strong effect on follower organizational identification with a one standard deviation increase in motivating language corresponding to over a half of a standard deviation increase in follower organizational identification. This influence comes partly through growth in a follower's cultural knowledge and fit, but also through a direct influence. Model testing occurred with subjects from the USA and India with the model fitting equally well in both nations. These findings have important implications for research and practice which are explained in the paper's discussion and conclusion section.